Answer:
C
Step-by-step explanation:
(2x-3)(4x+5)
=2x(4x+5)-3(4x+5)
=8x^2+10x-12x-15
=8x^2-2x-15
Answer:
-60/7 or -8 4/7 would be the answer
I thought they would be the same so I would go with B. 85
Answer:
1) C = 3
2) B = 5
3) C = 8
Step-by-step explanation:
Question 1)
We have:
![(2x+3)(4x-1)](https://tex.z-dn.net/?f=%282x%2B3%29%284x-1%29)
Distribute:
![=(2x+3)(4x)+(2x+3)(-1)](https://tex.z-dn.net/?f=%3D%282x%2B3%29%284x%29%2B%282x%2B3%29%28-1%29)
Distribute:
![=8x^2+12x-2x-3](https://tex.z-dn.net/?f=%3D8x%5E2%2B12x-2x-3)
Combine like terms:
![=8x^2+10x-(3)](https://tex.z-dn.net/?f=%3D8x%5E2%2B10x-%283%29)
Therefore, C = 3.
Question 2)
We have:
![(x+2) (2x^2+x-1)](https://tex.z-dn.net/?f=%28x%2B2%29%20%282x%5E2%2Bx-1%29)
Distribute:
![\displaystyle =(x+2)(2x^2)+(x+2)(x)+(x+2)( - 1)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%3D%28x%2B2%29%282x%5E2%29%2B%28x%2B2%29%28x%29%2B%28x%2B2%29%28%20-%201%29)
Distribute:
![=(2x^3+4x^2)+(x^2+2x)+(-x -2)](https://tex.z-dn.net/?f=%3D%282x%5E3%2B4x%5E2%29%2B%28x%5E2%2B2x%29%2B%28-x%20-2%29)
Combine like terms:
![=2x^3+(5)x^2+x-2](https://tex.z-dn.net/?f=%3D2x%5E3%2B%285%29x%5E2%2Bx-2)
Therefore, B = 5.
Question 3)
We have:
![(x+2)(x^2-3x-2)](https://tex.z-dn.net/?f=%28x%2B2%29%28x%5E2-3x-2%29)
Distribute:
![=(x+2)(x^2)+(x+2)(-3x)+(x+2)(-2)](https://tex.z-dn.net/?f=%3D%28x%2B2%29%28x%5E2%29%2B%28x%2B2%29%28-3x%29%2B%28x%2B2%29%28-2%29)
Distribute:
![=(x^3+2x^2)+(-3x^2-6x)+(-2x-4)](https://tex.z-dn.net/?f=%3D%28x%5E3%2B2x%5E2%29%2B%28-3x%5E2-6x%29%2B%28-2x-4%29)
Combine like terms:
![=x^3-x^2-(8)x-4](https://tex.z-dn.net/?f=%3Dx%5E3-x%5E2-%288%29x-4)
So, C = 8.
Step-by-step explanation:
I don't understand the question